2010
DOI: 10.1073/pnas.0906710107
|View full text |Cite
|
Sign up to set email alerts
|

Resource limitation is a driver of local adaptation in mycorrhizal symbioses

Abstract: Symbioses may be important mechanisms of plant adaptation to their environment. We conducted a reciprocal inoculation experiment to test the hypothesis that soil fertility is a key driver of local adaptation in arbuscular mycorrhizal (AM) symbioses. Ecotypes ofAndropogon gerardiifrom phosphorus-limited and nitrogen-limited grasslands were grown with all possible “home and away” combinations of soils and AM fungal communities. Our results indicate thatAndropogonecotypes adapt to their local soil and indigenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
578
6
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 609 publications
(619 citation statements)
references
References 55 publications
31
578
6
4
Order By: Relevance
“…The plants in our study, however, were grown under optimal conditions, which could explain this lack of dependency, and additionally the correlation found in our study of cortical tissue with nitrogen content may have influenced mycorrhizal colonization. Plant reduce C allocation to AM fungi, since it constitutes a significant cost to the host plant (Olsson et al 2005), and high nitrogen content may also reduce C supply to AM fungi (Olsson et al 2005;Johnson et al 2010); we also found that arbuscule abundance was negatively correlated with total nonstructural carbohydrates in roots. However, under stress conditions that occur with great regularity in the course of growth, the current lack of differences in mycorrhizal colonization can bring unexpected results in the form of weakening growth or descending the tree.…”
Section: Discussionsupporting
confidence: 54%
“…The plants in our study, however, were grown under optimal conditions, which could explain this lack of dependency, and additionally the correlation found in our study of cortical tissue with nitrogen content may have influenced mycorrhizal colonization. Plant reduce C allocation to AM fungi, since it constitutes a significant cost to the host plant (Olsson et al 2005), and high nitrogen content may also reduce C supply to AM fungi (Olsson et al 2005;Johnson et al 2010); we also found that arbuscule abundance was negatively correlated with total nonstructural carbohydrates in roots. However, under stress conditions that occur with great regularity in the course of growth, the current lack of differences in mycorrhizal colonization can bring unexpected results in the form of weakening growth or descending the tree.…”
Section: Discussionsupporting
confidence: 54%
“…2A). The Glomeromycota phylum is composed almost entirely of arbuscular mycorrhizal fungi (32), and we expected these fungi to decrease in relative abundance with nutrient additions because they would be less valuable to their hosts and thus provided with less plant C under conditions of increased N and P availability (33)(34)(35). We further investigated nutrient effects on mycorrhizal fungi by assessing the collective responses of mycorrhizal fungi, including those taxa outside the Glomeromycota phylum that are reported in the literature as being mycorrhizal.…”
Section: Resultsmentioning
confidence: 99%
“…Divergence in morphology has been a dominating theme of coevolutionary studies (for recent examples see e.g. Benkman et al 2012;Pauw et al 2009; Toju et al 2011), but studies of chemical diversification increasingly have shown that coevolution is just as often about attractants, repellents, toxic compounds, and counter responses to those compounds (Berenbaum and Zangerl 2006;Brodie and Ridenhour 2003;Ehrlich and Raven 1964;Foitzik et al 2003;Hanifin et al 2008;Johnson et al 2010;Raguso 2008;. Attractants are a particularly intriguing class of compounds in coevolving interactions, because they actively attract mutualists but may simultaneously attract enemies (Theis and Adler 2012).…”
Section: Introductionmentioning
confidence: 99%